2015
DOI: 10.1039/c5nr00620a
|View full text |Cite
|
Sign up to set email alerts
|

Contact angle and adsorption energies of nanoparticles at the air–liquid interface determined by neutron reflectivity and molecular dynamics

Abstract: Understanding how nanomaterials interact with interfaces is essential to control their self-assembly as well as their optical, electronic, and catalytic properties. We present here an experimental approach based on neutron reflectivity (NR) that allows the in situ measurement of the contact angles of nanoparticles adsorbed at fluid interfaces. Because our method provides a route to quantify the adsorption and interfacial energies of the nanoparticles in situ, it circumvents problems associated with existing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
82
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 49 publications
(61 reference statements)
1
82
0
Order By: Relevance
“…In the case of 4 He the coherent scattering length is 3.26 fm, with no incoherent scattering or significant neutron absorption. For 3 He, on the other hand, the situation is significantly different with a coherent scattering factor of 5.74 À 1.483i fm, where the imaginary number represents a resonant absorption term; it also has a significant incoherent scattering factor of À2.5… þ 2.568i fm that leads to a neutron scattering background.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of 4 He the coherent scattering length is 3.26 fm, with no incoherent scattering or significant neutron absorption. For 3 He, on the other hand, the situation is significantly different with a coherent scattering factor of 5.74 À 1.483i fm, where the imaginary number represents a resonant absorption term; it also has a significant incoherent scattering factor of À2.5… þ 2.568i fm that leads to a neutron scattering background.…”
Section: Introductionmentioning
confidence: 99%
“…In later experiments with neutron reflection from the free surfaces of commercially pure 4 He and of a 3 He- 4 He mixture with a 3 He concentration of 0.5% it was found that the addition of 3 He isotopic impurities could be leading to the formation of Andreev levels 7 at low temperatures (around 0.3 K) resulting in the formation of a diffusive 3 He nanolayer with a thickness of a few hundred Å on the bulk 4 He liquid surface. 8,9 Unfortunately, useful numerical analysis of the experimental data turned out to be impossible.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations